Proses Sekuritisasi Plastik di Uni Eropa: Studi Kasus Jerman, Perancis, Italia, Britania Raya, Luksemburg dan Irlandia - Wijayanti, Rahayu Hana; Basith Dir, Andi Akhmad (Journal of International Relations, 2020)
The use of plastic has been a complement to human life since commercial plastics were first discovered in 1833. Plastics are predicted as a ‘savior of the earth’ because it can reduce the energy use and reduce paper bags, also their versatile uses becoming one of the important factors of plastic in daily life. However, plastics are gradually becoming a ‘threat’ along with the declining popularity of plastics in the world including the European Union, as evidenced by the declining consumption and production of plastics as well as changes in public behavior in the European Union to become 'anti-plastic'. This research examines why there can be a decline in the popularity of plastics in the European Union regardless of their usefulness and the benefits that society can gain from using plastic. This research hypothesizes that those phenomenon results due to several important actors in the European Union, such as ENGO and Mass Media, Political Elite, Epistemic Community and the last is European Union Institution are constructing plastic issues as a threat. This study uses the Copenhagen Securitization Theory as an analysis knife to answer the above question. and observe sic different countries e.g Germany, France, Italy, United Kingdom, Luxembourg, and Ireland.